CASHLESS REVOLUTION: THE IMPACT ON REGIONAL ECONOMIC GROWTH - Abdilah, Mohamad; Andi Chairil Furqan; Dita Indriyani (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2025)
ABSTRACTThis study aims to examine the impact of non-cash payment systems on regional economic growth at the district and city levels in Indonesia. The variables analyzed include the transaction value of electronic money (e-money), ATM/debit cards, and credit cards. A quantitative approach was employed using secondary data from 984 districts and cities across Indonesia for the period 2020-2021, selected through purposive sampling. The data were evaluated using multiple linear regression analysis, which revealed that digital transactions particularly those using e-money and ATM/debit cards have a positive and significant influence on regional economic growth. In contrast, credit card usage was found to have no significant effect. These findings suggest that certain types of digital payment instruments can effectively stimulate local economic activity. Accordingly, local governments and regulators are encouraged to expand digital infrastructure and enhance financial literacy, with a particular focus on promoting inclusive and accessible non-cash payment tools such as e-money and debit cards. This research underscores the importance of adopting a region-based approach in designing economic digitalization policies and recommends that future studies explore the roles of social, cultural, and technological readiness factors in supporting the success of payment system transformation moving forward.Keywords: Economic growth; Non-cash payment systems; Electronic money; ATM/Debit cards; Credit cards ABSTRAKPenelitian ini bertujuan untuk mengkaji dampak sistem pembayaran nontunai terhadap pertumbuhan ekonomi regional di tingkat kabupaten dan kota di Indonesia. Variabel yang dianalisis meliputi nilai transaksi uang elektronik (e-money), kartu ATM/debit, dan kartu kredit. Pendekatan kuantitatif digunakan dengan menggunakan data sekunder dari 984 kabupaten dan kota di seluruh Indonesia untuk periode 2020-2021, yang dipilih secara purposive sampling. Data tersebut dievaluasi menggunakan analisis regresi linier berganda, yang mengungkapkan bahwa transaksi digital khususnya yang menggunakan e-money dan kartu ATM/debit memiliki pengaruh positif dan signifikan terhadap pertumbuhan ekonomi regional. Sebaliknya, penggunaan kartu kredit ditemukan tidak memiliki pengaruh yang signifikan. Temuan ini menunjukkan bahwa jenis instrumen pembayaran digital tertentu dapat secara efektif merangsang aktivitas ekonomi lokal. Oleh karena itu, pemerintah daerah dan regulator didorong untuk memperluas infrastruktur digital dan meningkatkan literasi keuangan, dengan fokus khusus pada promosi alat pembayaran nontunai yang inklusif dan mudah diakses seperti e-money dan kartu debit. Penelitian ini menggarisbawahi pentingnya mengadopsi pendekatan berbasis kawasan dalam merancang kebijakan digitalisasi ekonomi dan merekomendasikan agar studi masa depan mengeksplorasi peran faktor kesiapan sosial, budaya, dan teknologi dalam mendukung keberhasilan transformasi sistem pembayaran ke depannya.Kata Kunci: Pertumbuhan ekonomi; Sistem pembayaran non-tunai; Uang elektronik; Kartu ATM/Debit; Kartu Kredit